MENGEMBANGKAN KETERAMPILAN DESAIN GRAFIS PESERTA DIDIK DESA HEGARMANAH MENGGUNAKAN CANVA - Sutedi, Ade; Kamil, Zatnika Insan; Maulana, Fajar; Zahran, Fernuzuar Faiz; Rosarina, Risa; Hermansyah, M.fikri; Gopur, Muhammad; Nur Ihsan, Irsyad Ahmad; Sadiah, Rapiah; Nurlela, Nurlela; Jaelani, Akmal Abdul Kodir; Firginia, Rissky; Zahrahaq, Efica; Herian, Akmal Muh; Manikam, Menur; Aulya, Sofa Tsuroya Aulya; Malik, Luthfi Abdul; Hanan, Muhamad Ilham; Firmansyah, Lukman; Pratama, Guntur Eka; Iswandi, Wiky Asri (Jurnal PkM MIFTEK, 2023)
As a form of dedication to thematic Real Work Lecture (KKN) activities in Hegarmanah Village, the Writing Team took part in developing the education and knowledge of SMPN 3 Bayongbong students to be digitally literate. The aim is to develop creativity, innovation and skills in using technology, one of which is graphic design. The methods used in implementing this program are workshops and demonstrations, where students learn by being guided and then practice what they learn. This program involves outreach, training, implementation, and evaluation. The results of this program show an increase in students' understanding of graphic design, especially the use of the Canva application and design tools and related concepts to develop students' creativity and imagination in creating a Graphic Design. Apart from that, based on surveys obtained from the pre-test and post-test results of training participants, there was an increase in mastery and understanding of graphic design from 20% to 66%.